Covid-19: memories and collections under construction - Pereira Filho, Hilário Figueiredo (2021)
While some refuse to adopt practices of social isolation, unlike those who respect the recommendations of scientific institutions in the context of Covid-19, some initiatives sought to record the production of narratives and memories about experiences provided by the pandemic. From projects developed by public and private institutions, whose approaches vary between individual and collective dimensions, we seek to deepen the debates on the right to memory, on the access to archives as a democratic practice and the plural construction of representations about the present tensioned by uncertainties, traumas and hopes.